ISOLATION, CHARACTERISTICS, AND ANTIOXIDANT ACTIVITY OF LOW MOLECULAR COMPOUNDS OF FRUIT BODIES LACTARIUS PERGAMENUS (Fr.) Fr MUSHROOMS - Volodymir, Antonyuk; V. Tsivinska, Mariana; V. Panchak, Lydia; S. Stoika, Rostislav (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Methanol and methylene chloride extracts were obtained from fresh and dried fruit bodies of Lactarius pergamenus (Fr.) Fr. and studied by gas-chromatography mass spectrometry (GC/MS), thin-layer chromatography (TLC), and column chromatography on silica gel. Antioxidant activity of individual fractions of mushroom extracts was measured by using DPPH (1,1-diphenyl-2-picrylhydrazyl). Stearic acid was removed from the extracts by their freezing, and phthalic acid esters, sesquiterpene compounds, long chain fatty acids, and their derivatives were found after that GC/MS analysis showed that the most abundant antioxidant compounds in methylene chloride extracts are: velleral dialdehyde, azulene sesquiterpenes, leaf and pelargonic aldehydes, and oleic acid amide. The velleral is known to provide a pungent taste of Lactarius sp. mushrooms. Thus, the antioxidant properties of methanol and methylene chloride extracts of mushrooms of Lactarius genus are not caused by the presence of phenols, flavonoids, Î²-carotenes, and tocopherols, as it was suggested in other studies. High level of phthalates that was discovered in these mushrooms, probably, is play an important role in the mechanisms of defence of mushrooms from insects. The obtained data are important for controlling chemical composition during isolation of pharmacologically active substances, and for preparation of antifungal ointments, in particular.